Optimizing the Performance and Governance of MSMEs in the Special Region of Yogyakarta Through Digitalization - Aji, Juhari Sasmito; Pahlevi, Reza Widhar; Pribadi, Ulung; Fitria, Audita Arifa (Journal of Economics, Business, Accounting and Management, 2023)
A significant feature of technology is its capacity to change the routines and behavior of business players, especially MSMEs actors. MSMEs players in the Special Area have been impacted by the Covid-19 outbreak and are now looking to the MSMEs sector for business opportunities. It is necessary to overcome the difficulty of attaining the digitization of MSMEs. The fact that the MSMEs actors are not fundamentally and mentally equipped is another problem. The study's objective is to evaluate the effectiveness of using digital literacy, e-commerce, and skills as a tactic to enhance MSMEs governance and performance. The main sources of data for the study were imaginative MSMEs Daerah Istimewa Yogyakarta actors. The analytical unit of the study is the manager or owner of MSMEs in Daerah Istimewa Yogyakarta. In this study, primary data are gathered by a questionnaire. The sample size was established using a simple proportionate random sampling approach. The AMOS SEM analysis tool and a sample of 20% of all MSMEs in each district and city of the Daerah Istimewa Yogyakarta are used to achieve this. According to the study's findings, E-Commerce affects the MSMEs Governance, Digital Expertise affects MSMEs Governance and Performance, MSMEs Governance the performance of MSMEs. However, E-Commerce has no effect on the performance of MSMEs.